Anti-tumor necrosis factor agents in psoriasis: addressing key challenges using biosimilars. (2nd January 2021) - Prignano, Francesca; Choi, Jaeyun; Pieper, Burkhard; Iversen, Lars
ABSTRACT: Introduction: Anti-tumor necrosis factor agents are key treatment options in moderate–severe psoriasis. The advent of multiple biosimilars of these drugs provides a major opportunity to address this particular factor by helping to reduce costs. Reduced cost can help improve undertreatment, which is one of the challenges in treating moderate-severe psoriasis. There is now a wealth of real-world evidence demonstrating that patients with psoriasis can be initiated on – or transitioned to – an anti-TNF biosimilar without detrimental effects on overall safety and efficacy. Furthermore, recent results suggest that patients can be switched between different biosimilar versions of the same anti-TNF agent without any compromise in outcomes. Areas covered: In this review, we summarized the role of anti-TNFs in psoriasis, health economic aspects of anti-TNF biosimilars, and their real-world data in clinical practice and registries. Expert opinion: The introduction and competition of anti-TNF biosimilars reduced the cost of biologics and accumulated real-world data support efficacy and safety of anti-TNF biosimilars for psoriasis treatment. Although IL-17 and IL-23 inhibitors show better efficacy in psoriasis patients, long-term efficacy and safety data of anti-TNF and cost-effectiveness of anti-TNF biosimilars may play an important role to increase patient access to biologics through greater adoption of biosimilars.